Model Sistem Dinamik: Pengaruh Fasilitas Kampus terhadap Mutu Publikasi Ilmiah Mahasiswa Pascasarjana - Yusi Rahmaniar; Pudji Muljono; Adil Basuki Ahza (Program Studi Manajemen Pendidikan, 2023)
Abstract Starting from the circular of the Dirjen Dikti Number: 152/E/T/2012 concerning the publication of student scientific work, the Indonesian government encourages students to play an active role in conducting research publications. The quantity of scientific publications carried out by students must also be followed by good quality. In the world of education, the quality of scientific publications can be seen from the categories of research outputs and how the factors affect the field of research. Campus facilities are said to be one of the important factors in supporting the quality of student research publications. Because not only physically, non-physical facilities are considered very important to improve student competence and capabilities, for example in the form of training. Dynamic system analysis is a research methodology that can capture the condition of a quality management system. In this study the dynamic system was used to look at the quality of research publications conducted by postgraduate students, to see how facilities could affect the quality of student research publications.